Assessments at multiple levels of biological organization allow for an integrative determination of physiological tolerances to turbidity in an endangered fish species - Hasenbein, Matthias (Conserv Physiol, 2016)
Turbidity can influence trophic levels by altering species composition and can potentially affect fish feeding strategies and predator–prey interactions. The estuarine turbidity maximum, described as an area of increased suspended particles, phytoplankton and zooplankton, generally represents a zone with higher turbidity and enhanced food sources important for successful feeding and growth in many fish species. The delta smelt (Hypomesus transpacificus) is an endangered, pelagic fish species endemic to the San Francisco Estuary and Sacramento–San Joaquin River Delta, USA, where it is associated with turbid waters. Turbidity is known to play an important role for the completion of the species' life cycle; however, turbidity ranges in the Delta are broad, and specific requirements for this fish species are still unknown. To evaluate turbidity requirements for early life stages, late-larval delta smelt were maintained at environmentally relevant turbidity levels ranging from 5 to 250 nephelometric turbidity units (NTU) for 24 h, after which a combination of physiological endpoints (molecular biomarkers and cortisol), behavioural indices (feeding) and whole-organism measures (survival) were determined. All endpoints delivered consistent results and identified turbidities between 25 and 80 NTU as preferential. Delta smelt survival rates were highest between 12 and 80 NTU and feeding rates were highest between 25 and 80 NTU. Cortisol levels indicated minimal stress between 35 and 80 NTU and were elevated at low turbidities (5, 12 and 25 NTU). Expression of stress-related genes indicated significant responses for gst, hsp70 and glut2 in high turbidities (250 NTU), and principal component analysis on all measured genes revealed a clustering of 25, 35, 50 and 80 NTU separating the medium-turbidity treatments from low- and high-turbidity treatments. Taken together, these data demonstrate that turbidity levels that are either too low or too high affect delta smelt physiological performance, causing significant effects on overall stress, food intake and mortality. They also highlight the need for turbidity to be considered in habitat and water management decisions.